KERAGAAN HIBRIDAINTRA SPESIFIK DARIEMPAT STRAIN IKAN NILA (Oreochromis niloticus) DIKARAMBA JARING APUNG, DANAU LIDO, BOGOR - Prana Mahardhika; Rudhy Gustiano; Dinar Tri Soelistyowati; MH Fariduddin Ath-thar (BERITA BIOLOGI, 2011)
The objectives of the study was to evaluate hybrid performance of sixteen reciprocal cross resulted from three strains (Red NIFI,Nirwana, BEST) and one population (Lido Lake population) of nile tilapi. The study was conducted in experimental floating netcages in Lido Lake. Fish of 25 days old ranged 0,4 ± 0.07 g were used in the experiment. Fish were reared in floating net cages sized 2x1x1 m for each cross with the density of 50 fish/cage for eight weeks (56 days). Feed were given 10% of body weight with frequency three times a day. The results showed that the highest average larvae production was 1216 from Nirwana female crossed with four different male. Growth rate of hybrids were higher than the parents (P < 0.05) and the highest was .ed NIFI x c? BEST (6,440±0,0712% ).The highest survival rate was $ Red Lido x S BEST hybrid (77.0 ±2,78%")). For heterosis, Specific Growth Rate (SGR) was 5.8188% on hybrid between Nirwana and Red Lido. While for survival rate was 15.5888% on Nirwana x BEST hybrid. Crossing between fenotipe of light color background (red) and dark color background (black) showed that red color was dominant to the black one. Pleiotric effect of color gen was detected on the SGR and survival rate.